NILAI-NILAI AKHLAKUL KARIMAH DALAM NOVEL ANAK DI INDONESIA TAHUN 1921-2010 - Dewi Budi Purwati (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2011)
Children’s literature in Indonesia contains good values or akhlakul karimah which are useful for their education and the elements are relevant to their cognitive, psychological, and language developments. This study aims to identify and find out values of akhlakul karimah in the themes of children’s novels in Indonesia in 1921 – 2010 based on the structural approach and values of akhlak from the Islamic perspective. This study employed the qualitative descriptive method using the content analysis. The results of the analysis on the themes of children’s novel in 1921 – 2010 show that the dominant theme is friendship.